Absoluttest von rotationssymmetrischen Asphären mittels radialem Shearing - Mantel, Klaus; Geist, Eduard; Harder, Irina; Lindlein, Norbert (DGAO-Proceedings, 2010)

Absolutverfahren zum Nulltest asphärischer Linsen im Durchlicht - Berger, Andreas; Mantel, Klaus; Harder, Irina; Lindlein, Norbert (114. Jahrestagung der DGaO, 2013)

Adaptive frequency comb illumination for interferometry in the case of nested two-beam cavities - Harder, Irina; Leuchs, Gerd; Mantel, Klaus Peter; Schwider, Johannes (Applied Optics, 2011)

Adjustable diffractive spiral phase plates - Harn, Walter; Bernet, Stefan; Ritsch-Marte, Monica; Harder, Irina; Lindlein, Norbert (Optics Express, 2015)

Artiffcial wave plates made from subwavelength structures - Rothau, Sergej; Ghadyani, Zahra; Harder, Irina; Lindlein, Norbert (113. Jahrestagung der DGaO, 2012)

Computer generiertes Hologramm als punktsymmetrische Streuplatte - Hampp, Heiko; Harder, Irina; Lano, Maik; Lindlein, Norbert (DGaO-Proceedings 2010 - http://www.dgao-proceedings.de - ISSN: 1614-8436, 2010)

Concentric ring metal grating for generating radially polarized light - Ghadyani, Zahra; Harder, Irina; Lindlein, Norbert; Berger, Andreas; Iff, Wolfgang; Vartiainen, Ismo; Kuittinen, M (Applied Optics, 2011)

Design and fabrication of nanowire metal grating polarizers for a shearing interferometer using polarization marking - Ghadyani, Zahra; Harder, Irina; Rusina, Olga; Iff, Wolfgang; Nercissian, Vanusch; Mantel, Klaus Peter; Lindlein, Norbert; Leuchs, Gerd (Proceedings of the EOS Topical Meeting on Diffractive Optics 2010, 2010)

Design considerations for the absolute testing approach of aspherics using combined diffractive optical elements - Lindlein, Norbert; Schwider, Johannes; Harder, Irina; Mantel, Klaus Peter; Khan, Gufran S. (Applied Optics, 2007)
Aspheric optical surfaces are often tested using diffractive optics as null elements. For precise measurements, the errors caused by the diffractive optical element must be calibrated. Recently, we reported first experimental results of a three position quasi-absolute test for rotationally invariant aspherics by using combined-diffractive optical elements (combo-DOEs). Here we investigate the effects of the DOE substrate errors on the proposed calibration procedure and present a set of criteria for designing an optimized combo-DOE. It is demonstrated that this optimized design enhances the overall consistency of the procedure. Furthermore, the rotationally varying part of the surface deviations is compared with the rotationally varying deviations obtained by an N-position averaging procedure and is found to be in good agreement. © 2007 Optical Society of America.
UnivIS-Import:2015-04-14:Pub.2007.nat.dphy.optik.1optik.design_9

Diffractive complete lateral shearing interferometer with reduced coherence - Harder, Irina; Nercissian, Vanusch; Schwider, Johannes; Berger, Andreas; Mantel, Klaus Peter; Lindlein, Norbert (Proceedings of the EOS Topical Meeting on Diffractive Optics 2010, 2010)

Diffractive simultaneous bidirectional shearing interferometry using tailored spatially coherent light - Nercissian, Vanusch; Harder, Irina; Mantel, Klaus Peter; Berger, Andreas; Leuchs, Gerd; Lindlein, Norbert; Schwider, Johannes (Applied Optics, 2011)

Diffraktive optische Elemente zur Lichtmanipulation - Schwider, Johannes; Dresel, Thomas; Beyerlein, Mathias; Harder, Irina; Lindlein, Norbert; Collischon, Martin; Leuchs, Gerd (2001)
UnivIS-Import:2015-04-14:Pub.2001.nat.dphy.optik.1optik.diffra

Diffraktives 2D-Shearing-Interferometer mit partieller rÃa4umlicher KohÃa4renz - Nercissian, Vanusch; Mantel, Klaus; Harder, Irina; Berger, Andreas; Schwider, Johannes; Lindlein, Norbert (DGaO-Proceedings, 2010)

Discontinuous space variant sub-wavelength structures for generating radially polarized light in visible region - Ghadyani, Zahra; Rothau, Sergej; Lindlein, Norbert; Leuchs, Gerd; Lohse, Olga; Harder, Irina (Journal of the European Optical Society: Rapid Publications, 2011)

Drei-Stellungstest für Asphären: Steigerung der Genauigkeit - Geist, Eduard; Mantel, Klaus Peter; Harder, Irina; Lindlein, Norbert (DGAO-Proceedings, 2010)
Keywords: Jahrestagung der DGaO

Effect of fabrication errors on the diffraction pattern produced by sawtooth gratings - Harder, Irina; Lindlein, Norbert; Torcall-Milla, Francisco Jose (Applied Optics, 2010)

Evaluation algorithms for multistep measurement of spatially varying linear polarization and phase - Berger, Andreas; Nercissian, Vanusch; Mantel, Klaus Peter; Harder, Irina (Optics Letters, 2012)

Flexible beam shaping system using fly's eye condenser - Lindlein, Norbert; Lano, Maik; Zimmermann, Maik; Bich, Andreas; Eisner, Martin; Harder, Irina; Voelkel, Reinhard; Weible, Ken (Applied Optics, 2010)
Normally, fly's eye condensers are used to homogenize light. However, in the case of fully coherent light, a fly's eye condenser, in connection with some simple optical elements, such as a diffractive axicon, a grating, and a telescope, can be used as a quite flexible beam shaping system, forming arrays of rings, parts of rings, or other structures with varying diameters. We present the principle, some simulation results, and some first experimental results. © 2010 Optical Society of America.

Form birefringent quarter wave plate for polarization conversion - Ghadyani, Zahra; Rothau, Sergej; Russina, Olga; Harder, Irina; Lindlein, Norbert (37th International Conference on Micro and Nano Engineering, 2011)

Generation of a wave packet tailored to efficient free space excitation of a single atom - Golla, Andrea; Chalopin, Benoit; Bader, Marianne; Harder, Irina; Mantel, Klaus; Maiwald, Robert; Lindlein, Norbert; Sondermann, Markus; Leuchs, Gerd (European Physical Journal D, 2012)
We demonstrate the generation of an optical dipole wave suitable for the process of efficiently coupling single quanta of light and matter in free space. We employ a parabolic mirror for the conversion of a transverse beam mode to a focused dipole wave and show the required spatial and temporal shaping of the mode incident onto the mirror. The results include a proof of principle correction of the parabolic mirror's aberrations. For the application of exciting an atom with a single photon pulse, we demonstrate the creation of a suitable temporal pulse envelope. We infer coupling strengths of 89% and success probabilities of up to 87% for the application of exciting a single atom for the current experimental parameters. © EDP Sciences, Società Italiana di Fisica, Springer-Verlag 2012.

Homogenization and beam shaping with micro lens arrays - Harder, Irina; Lano, Maik; Lindlein, Norbert; Schwider, Johannes (Proceedings of SPIE, 2004)
UnivIS-Import:2015-04-14:Pub.2004.nat.dphy.optik.1optik.homoge

Interferometric quasi-absolute tests for aspherics using a radial shear position - Mantel, Klaus Peter; Geist, Eduard; Harder, Irina; Lindlein, Norbert; Leuchs, Gerd (Optics Letters, 2009)
Increasing accuracy requirements in aspheric metrology make the development of absolute testing procedures for aspheric surfaces important. One strategy is transferring the standard practice three-position test for spheres to aspherics. The three-position test, however, involves a cat's eye position and therefore has certain drawbacks. We propose an absolute testing method for rotationally symmetric aspherics where the cat's eye position is replaced with a radially sheared position. Together with rotational movements of the specimen, the surface deviations can be obtained in an absolute manner. To demonstrate the validity of the procedure, we present a measurement result for a sphere and compare it with a result obtained by the standard three-position test. © 2009 Optical Society of America.
UnivIS-Import:2015-04-14:Pub.2009.nat.dphy.optik.1optik.interf

Künstliche nanostrukturierte Polarisationselemente - Rothau, Sergej; Harder, Irina; Lindlein, Norbert (114. Jahrestagung der DGaO, 2013)

Measuring the modulus of the spatial coherence function using an error tolerant phase shifting algorithm and a continuous lateral shearing interferometer - Harder, Irina; Eisner, Martin; Voelkel, Reinhard; Rothau, Sergej; Schwider, Johannes; Schwider, Peter Mario (Optics Express, 2016)
The modulus of the degree of coherence can be derived from interference patterns either by using fringes and next neighbour operations or by using several interferograms produced through phase shifting. Here the latter approach will be followed by using a lateral shearing interferometer exploiting a diffractive grating wedge providing a linearly progressive shear. Phase shifting methods offer pixel-oriented evaluations but suffer from instabilities and drifts which is the reason for the derivation of an error immune algorithm. This algorithm will use five π/2-steps of the reference phase also for the calculation of the modulus of the coherence function.

Measuring the modulus of the spatial coherence function using an error tolerant phase shifting algorithm - Rothau, Sergej; Schwider, Johannes; Harder, Irina (117. Annual Meeting of the DGaO, 2016)

Optimised exposure strategies for artifial waveplates - Harder, Irina; Lohse, Olga; Rothau, Sergej; Piaszenski, Guido (39th International Conference on Micro and Nano Engineering, 2013)

Parallel two-step phase-shifting point-diffraction interferometry for microscopy based on a pair of cube beamsplitters - Peng, Gao; Yao, Baoli; Min, Junwei; Harder, Irina; Nercissian, Vanusch; Mantel, Klaus; Guo, Rongli; Zheng, Juanjuan; Ye, Tong (Optics Express, 2011)

Phase and polarization measurement of a spatially varying linear polarization distribution - Rothau, Sergej; Nercissian, Vanusch; Berger, Andreas; Harder, Irina; Mantel, Klaus Peter; Lindlein, Norbert (7th International Workshop on Advanced Optical Imaging and Metrology, Fringe 2013, 2013)
The first measurements show very good results and are consistent with the theory. The next step is the study of measurement results made with further combinations of φi and ωi and the investigation of their robustness against stochastic errors or the influence of elliptical polarization. © Springer-Verlag Berlin Heidelberg 2014.

Phase measurement of a spatially varying polarization distribution - Nercissian, Vanusch; Geier, Florian; Berger, Andreas; Rothau, Sergej; Ghadyani, Zahra; Harder, Irina; Mantel, Klaus Peter; Lindlein, Norbert (DGaO Proceedings, 2012)

Phase-shift extraction for generalized phase-shifting interferometry - Peng, Gao; Yao, Baoli; Lindlein, Norbert; Mantel, Klaus Peter; Harder, Irina; Geist, Eduard (Optics Letters, 2009)
A simple algorithm for blind extraction of phase shifts is proposed for generalized phase-shifting interferometry from only three interferograms. Based on the statistical property of the object wave, the algorithm calculates approximately the involved phase shifts as initial values. The extraction is further improved by an iterative method, considering the fact that the closer the phase shifts approach their real values, the more uniform the reconstructed reference wave will become. The feasibility of this algorithm is demonstrated by both simulation and experiment. © 2009 Optical Society of America.
UnivIS-Import:2015-04-14:Pub.2009.nat.dphy.optik.1optik.phases

Phase-shifting point-diffraction interferometry with common-path and in-line configuration for microscopy - Peng, Gao; Harder, Irina; Nercissian, Vanusch; Mantel, Klaus; Yao, Baoli (Optics Letters, 2010)

Phase-shifting Zernike phase contrast microscopy for quantitative phase measurement - Peng, Gao; Yao, Baoli; Harder, Irina; Lindlein, Norbert; Torcall-Milla, Francisco Jose (Optics Letters, 2011)

Previous Record Record 8 of 11 Next Record Record from Web of Science® On the calibration of diffractive nulls for transmission tests of aspheric components - Schwider, Johannes; Lindlein, Norbert; Mantel, Klaus Peter; Harder, Irina (Optics Communications, 2007)
UnivIS-Import:2015-04-14:Pub.2007.nat.dphy.optik.1optik.previo

Reduktion der Residuenanzahl bei lateraler Speckle-Shearing-Interferometrie: Simulationen und Messergebnisse - Nercissian, Vanusch; Mantel, Klaus Peter; Harder, Irina; Lindlein, Norbert (115. Jahrestagung der DGaO, 2014)

Reduktion von Phasensingularitäten bei lateraler Shearing-Speckle-Interferometrie - Nercissian, Vanusch; Mantel, Klaus Peter; Seifert, Kristina Johanna; Berger, Andreas; Harder, Irina; Lindlein, Norbert (114. Jahrestagung der DGaO, 2013)

Refraktive Strahlformungsoptik mittels direktschreibender Grautonlithographie - Leroch, Dominik; Harder, Irina; Lindlein, Norbert (114. Jahrestagung der DGaO, 2013)

Stitching errors in diffractive nulltest elements - Berger, Andreas; Harder, Irina; Nercissian, Vanusch; Mantel, Klaus Peter; Lindlein, Norbert (DGaO Proceedings, 2012)

Strukturierungsfehler diffraktiv optischer Elemente - Berger, Andreas; Harder, Irina; Lohse, Olga; Lindlein, Norbert (114. Jahrestagung der DGaO, 2013)